Factor shares and income inequality - Empirical evidence from Germany 2002 - 2008 - Martin Adler; Kai Daniel Schmid (University of Tübingen, Faculty of Economics and Social Sciences, 2012)
We examine the interplay between changes in the functional distribution of income and the distribution of market income among households. We use micro data from the German Socio-Economic Panel as well as macro data from the German Federal Statistical Office from 2002 to 2008. We categorize and evaluate the implications of changes in the functional distribution of income upon the distribution of income among individuals on the basis of a simple theoretic framework that links the degree of the concentration of income from asset flows among individuals to the (structural) relationship between individuals' levels of market income and their respective income shares from asset flows. Our empirical analysis offers two insights: First, the relative rise of income from asset flows reported by German National Accounting Statistics is also evident in the micro data taken from the German Socio-Economic Panel. Second, rising capital income shares are associated with an increasing concentration of market income.
urn:nbn:de:bsz:21-opus-62222
Keywords: D31; D33; E6; E25; 330; Factor Shares; Income Distribution; Inequality; Market Income; Funktionelle Einkommensverteilung; Einkommensverteilung; Soziale Ungleichheit; Gewinnquote; Deutschland